MEDIA INTERAKSI PEMBELAJARAN UNTUK MENINGKATKAN PENGETAHUAN PENCEGAHAN COVID-19 PADA ANAK SEKOLAH DASAR - Siti Wasliyah (Politeknik Kesehatan Kementerian Kesehatan Banten, 2023)
The World Health Organization (WHO) has planned Covid-19 preparedness and response since February 3, 2020. Covid-19 is a pandemic that is felt by all levels of society, including children. Prevention efforts are continuously carried out for all levels of society, including education through various media, both through television and social media. Indonesian children need to be provided with information about the culture of self-protection against disasters, especially pandemic disasters because children are always in contact with peers while playing. The existence of a policy regarding studying from home/school from home during the Covid-19 pandemic made more children access video media for learning media. Learning interaction media in the form of interesting videos is applied to increase the knowledge of school-age children about the Covid-19 prevention protocol. This study is a quasi-experimental study with a pretest and post-test group design approach, which aims to identify the effect of learning interaction media on knowledge of the Covid-19 prevention protocol. The study was conducted in August - December 2020 with a population of students at Islamic City Elementary School Kota Tangerang. The sampling method used was Consecutive sampling totaling 44 respondents. The results showed that there was an increase in the ability of each intervention and control group, and there were significant differences in the measurements before and after the intervention (p Value 0.001). In the statistical test of the two groups, the p Value was 0.016 (p-Value ≤ 0.005), so it can be concluded that there was a significant difference in mean between the intervention group and the control group, where the average group with video was higher than the group without video.